Direct costs of glaucoma and severity of the disease: a multinational long term study of resource utilisation in Europe. Issue 10 (16th September 2005) - Traverso, C E; Walt, J G; Kelly, S P; Hommer, A H; Bron, A M; Denis, P; Nordmann, J-P; Renard, J-P; Bayer, A; Grehn, F; Pfeiffer, N; Cedrone, C; et al.
Abstract : Background: Resource utilisation and direct costs associated with glaucoma progression in Europe are unknown. As population progressively ages, the economic impact of the disease will increase. Methods: From a total of 1655 consecutive cases, the records of 194 patients were selected and stratified by disease severity. Record selection was based on diagnoses of primary open angle glaucoma, glaucoma suspect, ocular hypertension, or normal tension glaucoma; 5 years minimum follow up were required. Glaucoma severity was assessed using a six stage glaucoma staging system based on static threshold visual field parameters. Resource utilisation data were abstracted from the charts and unit costs were applied to estimate direct costs to the payer. Resource utilisation and estimated direct cost of treatment, per person year, were calculated. Results: A statistically significant increasing linear trend (p = 0.018) in direct cost as disease severity worsened was demonstrated. The direct cost of treatment increased by an estimated €86 for each incremental step ranging from €455 per person year for stage 0 to €969 per person year for stage 4 disease. Medication costs ranged from 42% to 56% of total direct cost for all stages of disease. Conclusions: These results demonstrate for the first time in Europe that resource utilisation and direct medical costs of glaucoma management increase with worsening disease severity. Based on these findings, managing glaucoma and effectively delaying disease progression would be expected to significantly reduce the economic burden of this disease. These data are relevant to general practitioners and healthcare administrators who have a direct influence on the distribution of resources.